2023
DOI: 10.3390/antibiotics12050941
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance of Escherichia coli Isolates from Livestock and the Environment in Extensive Smallholder Livestock Production Systems in Ethiopia

Abstract: The objective of this study was to characterize the distribution of antimicrobial resistance (AMR) of Escherichia coli (E. coli) isolated from livestock feces and soil in smallholder livestock systems. A cross-sectional study was carried out sampling 77 randomly selected households in four districts representing two agroecologies and production systems. E. coli was isolated and the susceptibility to 15 antimicrobials was assessed. Of 462 E. coli isolates tested, resistance to at least one antimicrobial was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
6

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 59 publications
1
6
6
Order By: Relevance
“…AMP and TE had the highest proportion of resistant isolates of E. coli from goats, whereas CHL had the highest susceptibility. This finding is not comparable with that of goats raised in the silvopastoral system, where the level of resistance to TE was lower (13.6%) than in the present study [25]. Notwithstanding, our findings are consistent with those of a similar study conducted in Nigeria, where E. coli isolates from goat feces exhibited high resistance levels to AMP (94.7%) and TE (89.5%) [57].…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…AMP and TE had the highest proportion of resistant isolates of E. coli from goats, whereas CHL had the highest susceptibility. This finding is not comparable with that of goats raised in the silvopastoral system, where the level of resistance to TE was lower (13.6%) than in the present study [25]. Notwithstanding, our findings are consistent with those of a similar study conducted in Nigeria, where E. coli isolates from goat feces exhibited high resistance levels to AMP (94.7%) and TE (89.5%) [57].…”
Section: Discussioncontrasting
confidence: 95%
“…The prevalence of AMP (49%) and TE resistance (23%) observed in cattle production in the forest interface system aligned with the findings reported previously [52]. In addition, a study [25] reported significantly high resistance levels against TEs in isolates collected from cattle raised in the silvopastoral system of Ethiopia. Consistent with the findings of the current study, E. coli isolates from the cattle production systems of Zimbabwe (78%), Ghana (54.8%), Mexico (68.8%), and Indonesia (35.5%) demonstrated simihigh levels of resistance against AMP [53][54][55][56].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In Italy, the prevalence was 23.3% [37], whereas in France, the prevalence was 5%, and in Japan, it reached 5.2% [38]. In Africa, fecal samples of Ethiopian cattle have a higher prevalence (52%) [39], whereas broiler farms in Zambia have reported lower values [40]. Pig farms in Nigeria recorded 41.2% [41], Cameroon recorded 59.1% [42], and Kenya had the highest value at 81% [43].…”
Section: Worldwide Prevalence Of Esbl E Coli In Livestockmentioning
confidence: 96%